Newsprints - Xu, Ru. (New York : Graphix, 2017)
With her city at war, orphan Blue disguises herself as a newsboy for the only local paper that tells the truth, but a new friend gives her the courage to start seeking the freedom to be herself.
School Library Journal starred, December 2016.
Publisher's Weekly, October 2016.
Booklist, December 2016.
Kirkus Review, November 2016.
2.7
3-6
Keywords: Newspaper carriers -- Comic books, strips, etc. -- Juvenile fiction; Orphans -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Newspaper carriers -- Fiction; Orphans -- Fiction; Friendship -- Fiction; Newspaper carriers -- Comic books, strips, etc. -- Fiction; Orphans -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips,etc. -- Fiction; Orphans -- Fiction; Graphic novels; Comics (Graphic works)